2014
DOI: 10.1111/apt.12886
|View full text |Cite
|
Sign up to set email alerts
|

The severity of circulating neutrophil dysfunction in patients with cirrhosis is associated with 90‐day and 1‐year mortality

Abstract: SUMMARY BackgroundPatients with cirrhosis are susceptible to sepsis, pre-disposing to the development of encephalopathy, bleeding and organ dysfunction with associated high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 27 publications
2
83
0
1
Order By: Relevance
“…'Paralysed' monocytes with reduced monocyte HLA-DR expression have been shown to be an independent predictor of poor outcome in patients with decompensated cirrhosis [17] and neutrophil bacteriocidal capability is impaired with the most significant dysfunction being observed in those with advanced disease and in those treated with propranolol. This circulating neutrophil dysfunction has been shown to predict the development of infection, organ dysfunction and survival at 90 days and 1 year [18]. Interestingly, it has been shown that ammonia itself can induce neutrophil malfunction with excessive and inappropriate release of reactive oxygen species and failure to move towards and phagocytose bacteria such as Escherichia coli, which may offer some insight as to why ammonia and inflammation may be synergistic partners in the pathogenesis of HE [19].…”
mentioning
confidence: 98%
“…'Paralysed' monocytes with reduced monocyte HLA-DR expression have been shown to be an independent predictor of poor outcome in patients with decompensated cirrhosis [17] and neutrophil bacteriocidal capability is impaired with the most significant dysfunction being observed in those with advanced disease and in those treated with propranolol. This circulating neutrophil dysfunction has been shown to predict the development of infection, organ dysfunction and survival at 90 days and 1 year [18]. Interestingly, it has been shown that ammonia itself can induce neutrophil malfunction with excessive and inappropriate release of reactive oxygen species and failure to move towards and phagocytose bacteria such as Escherichia coli, which may offer some insight as to why ammonia and inflammation may be synergistic partners in the pathogenesis of HE [19].…”
mentioning
confidence: 98%
“…Functional defects include decreased phagocytic capacity [35] but preserved bacterial killing [36] and impaired chemotaxis and migration to sites of infection [37].…”
Section: Infection Related Mortality In Acute-on-chronic Liver Failurementioning
confidence: 99%
“…Exhaustion of immune effector cells is a plausible result of this overwhelming effect. Indeed, neutrophils demonstrate impaired bactericidal capacity in both ALF and cirrhosis and this predicts the development of organ dysfunction, infection and mortality (Taylor et al 2013(Taylor et al , 2014. Monocytes have also been shown to exhibit reduced antigen presenting capabilities and TNF-α production in liver failure (Berry et al 2011).…”
Section: Systemic Inflammation and Hepatic Encephalopathymentioning
confidence: 99%